Port stakeholder perceptions of Sandy impacts: a case study of Red Hook, New York. Issue 7 (2nd October 2020) - Ryan-Henry, John; Becker, Austin
ABSTRACT: Understanding the impacts of coastal storm hazards on all maritime port system stakeholders (e.g. operators, tenants, clients, workers, communities, governments) is essential to comprehensive climate change resilience planning. While direct damages and indirect impacts are quantifiable through economic data and modeling, qualitative data on the intangible consequences of storms are necessary to explicate interdependencies between stakeholders as well as conditions that substantially affect response and recovery capacities. This case study explores Hurricane Sandy storm impacts using evidence solicited from stakeholder representatives and extracted from contemporaneous and technical accounts of storm impacts on the port system at Red Hook Container Terminal, Brooklyn, New York, USA. Results highlight the wide range of direct damages, indirect costs, and intangible consequences impacting stakeholders across institutional boundaries and requiring coordination for recovery, providing insight into stakeholder relationships and dependencies in the post-disaster response and recovery process that are often not fully accounted for in current vulnerability assessment and response planning methodologies.